Verification of simulated ASIC functionality and radiation tolerance for the HL-LHC ATLAS ITk Strip Detector. (1st January 2023) - Ashmanskas, W.J.; Dandoy, J.R.; Dressnandt, N.C.; Keener, P.T.; Kroll, J.; Lipeles, E.; Lu, S.; Newcomer, F.M.; Nikolica, A.; Rosser, B.J.; Thomson, E.
Abstract: The verification of ASICs through simulation is critical to ensure their successful operation in particle physics detectors and to minimize the number of long and expensive production cycles required. Three radiation-tolerant ASICs (HCC, AMAC, and ABC) will perform the front-end readout, monitoring, and control of the ITk Strip charged-particle tracker for the ATLAS detector at the HL-LHC. The Python-based cocotb verification framework is used to design sophisticated tests with contributions from ASIC verification non-experts and students. The verification program includes interactions between multiple ASICs, realistic data flows, operational stress tests, and a focus on mitigation of disruptive Single Event Effects due to radiation.